Training-Induced Improvement of Response Selection and Error Detection in Aging Assessed by Task Switching: Effects of Cognitive, Physical, and Relaxation Training - Gajewski, Patrick D.; Falkenstein, Michael (Frontiers in Human Neuroscience, 2012)
Cognitive control functions decline with increasing age. One of them is response selection that forms the link between the goals and the motor system and is therefore crucial for performance outcomes in cognitive tasks. The present study examines if different types of group-based and trainer-guided training effectively enhance performance of older adults in a task switching task, and how this expected enhancement is reflected in electrophysiological brain activity, as measured in event-related potentials (ERPs). 141 healthy participants aged 65 years and older were randomly assigned to one of four groups: physical training (combined aerobic and strength-training), cognitive training (paper-pencil and computer-aided), relaxation and wellness (social control group) and a no-contact control group that did not receive any intervention. Training sessions took place twice a week for 90 minutes for a period of 4 months. The results showed a greater improvement of performance for attendants of the cognitive training group compared to the other groups. This improvement was evident in a reduction of mixing costs in accuracy and intraindividual variability of speed, indexing improved maintenance of multiple task-sets in working memory and an enhanced coherence of neuronal processing. These findings were supported by event-related brain potentials (ERP) which showed higher amplitudes in a number of potentials associated with response selection (N2), allocation of cognitive resources (P3b) and error detection (Ne). Taken together, our findings suggest neurocognitive plasticity of aging brains which can be stimulated by broad and multilayered cognitive training and assessed in detail by electrophysiological methods.